2022
DOI: 10.1093/treephys/tpac060
|View full text |Cite|
|
Sign up to set email alerts
|

PtoMYB142, a poplar R2R3-MYB transcription factor, contributes to drought tolerance by regulating wax biosynthesis

Abstract: Drought is one of the main environmental factors that limit plant development and growth. Accordingly, plants have evolved strategies to prevent water loss under drought stress, such as stomatal closure, maintenance of root water uptake, enhance of stem water transport, synthesis and deposition of cuticular wax. However, the molecular evidence of cuticular wax biosynthesis regulation in response to drought is limited in woody plants. Here, we identified a MYB transcription factor PtoMYB142 in response to droug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Research related to the function of the R2R3-MYB transcription factor has mainly focused on the herbaceous model species A. thaliana , and approximately 80% of functional research on AtR2R3-MYB genes has been reported [ 11 , 19 , 59 , 60 ]. Only a few drought-related R2R3-MYB genes, such as PtoMYB142 and PtrMYB94 , have been reported in poplar as a woody model species [ 16 , 18 ]. Furthermore, the study characterized the drought-inducible expression patterns of 10 PdMYB2R genes across different tissues in poplar NL895.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research related to the function of the R2R3-MYB transcription factor has mainly focused on the herbaceous model species A. thaliana , and approximately 80% of functional research on AtR2R3-MYB genes has been reported [ 11 , 19 , 59 , 60 ]. Only a few drought-related R2R3-MYB genes, such as PtoMYB142 and PtrMYB94 , have been reported in poplar as a woody model species [ 16 , 18 ]. Furthermore, the study characterized the drought-inducible expression patterns of 10 PdMYB2R genes across different tissues in poplar NL895.…”
Section: Discussionmentioning
confidence: 99%
“…PtoMYB170 plays a role in lignin deposition during poplar wood formation and can also reduce the rate of water evaporation by closing foliar stomata [ 17 ]. PtoMYB142 can directly bind to the promoters of wax biosynthesis genes (e.g., CER4 and KCS6 ) and induce their expression, resulting in increased wax accumulation in poplar leaves to adapt to water scarcity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cuticle is a polyester that is partly covered with waxes (epicuticular and intracuticular) ( Serrano et al., 2014 ). A study found PtoMYB142 could directly regulate the transcriptional activity of wax biosynthesis genes, e.g ., fatty acid hydroxylase ( CER4 ) and 3-ketoacyl CoA synthase ( KCS6 ), to adapt drought conditions for poplars ( Song et al., 2022 ). But the contribution of wax biosynthesis on poplar disease resistance is poorly studied.…”
Section: Defense Responses Of Poplars To Fungal Pathogensmentioning
confidence: 99%
“…Overexpression of GhMYB36 conferred drought tolerance in cotton and other plant species [ 16 ]. Overexpression of PtoMYB142 in poplar significantly enhanced drought resistance [ 17 ]. Overexpression of MbMYB108 from Malus baccata improved cold and drought resistance in Arabidopsis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%